Environmental imaginaries of the Middle East and North Africa - Davis, Diana K.; Burke, Edmund, III, 1940- (Ohio University Press series in ecology and history., 2011)
The landscapes of the Middle East have captured our imaginations throughout history. Images of endless golden dunes, camel caravans, isolated desert oases, and rivers lined with palm trees have often framed written and visual representations of the region. Embedded in these portrayals is the common belief that the environment, in most places, has been deforested and desertified by centuries of misuse. It is precisely such orientalist environmental imaginaries, increasingly undermined by contemporary ecological data, that the eleven authors in this volume question. This is the first volume t.